Taking the Wheel. Women and the Coming of the Motor Age - Anne Trine Larsen (The Royal Danish Library, 2004)
Anne Trine Larsen anmelder "Taking the Wheel. Women and the Coming of the Motor Age" af Virginia Scharff.